Wintertime aerosol in Las Vegas, Nevada - Brown, Steven G., author; Collett, Jeffrey L., advisor; Kreidenweis, Sonia, committee member; Roberts, Paul, committee member; Heald, Colette, committee member; Marchese, Anthony, committee member (Colorado State University. Libraries, 2014)
Numerous studies have found adverse health effects in subjects who live next to major roadways due to air pollution; in particular, there can be severe impacts on lung function and development in children living and/or attending school next to major roadways due to their exposure to air pollutants, including particulate matter (PM) or aerosol. The composition of aerosol at an elementary school next to a major freeway in Las Vegas, Nevada during winter 2008 was measured using a suite of measurements. An Aerodyne High Resolution Aerosol Mass Spectrometer (HR-AMS) was used to quantify the composition of non-refractory PM1 aerosol, including organic matter (OM); an Aethalometer was used to quantify black carbon (BC); a Sunset OCEC analyzer was used to measure organic and elemental carbon (OC, EC); and a particle-into-liquid system (PILS) coupled to two ion chromatographs (IC) was used to measure fine particle ions. Hi-volume PM2.5 samplers were used to collect aerosol on quartz fiber filters at between 2 and 24 hour intervals during the study, a subset of which were analyzed for PAHs and the biomass burning tracer levoglucosan. Data were analyzed by positive matrix factorization (PMF) to determine the amount of fresh, hydrocarbon-like organic aerosol (HOA), more oxidized OA (low-volatility and semi-volatile OA [LV-OOA, SV-OOA]) and biomass burning OA (BBOA). PM1 aerosol was predominantly carbonaceous, with OM plus BC accounting for 74% of the overall average 6.9 μg/m3 of PM measured. BC had a diurnal pattern similar to traffic volume, while OM was higher in the evening compared to the morning. OM was a mixture of fresh HOA, urban- and regional-scale OOA, and BBOA; in the evening, SV-OOA and BBOA peaked, while HOA concentrations were on average the same in the morning and evening, similar to BC. OM/OC ratios were low (1.52 ±0.14 on average) during the morning rush hour (average OM = 2.4 μg/m3) when vehicular emissions dominate this near-road measurement site, and even lower (1.46 ± 0.10) in the evening (average OM=6.3 μg/m3), when a combination of vehicular and fresh residential biomass burning emissions was typically present during a period characterized by strong atmospheric stability. While nitrate and sulfate had size distributions typical of secondary species with a sharp peak in particle diameter between 400 nm and 500 nm, OM had a broader distribution between 100 nm and 400 nm diameter particles, reflecting its combination of fresh, smaller particles and aged, larger particles. OM concentrations were on average similar between periods when the sampling site was upwind and downwind of the freeway, though during the morning OM concentrations were higher under downwind conditions, as was the fraction of HOA.
Keywords: black carbon; aerosol mass spectrometry; atmospheric chemistry; near-road; organic aerosol; receptor modeling